2015
DOI: 10.1037/cou0000015
|View full text |Cite|
|
Sign up to set email alerts
|

Etiology beliefs moderate the influence of emotional self-control on willingness to see a counselor through help-seeking attitudes among Asian American students.

Abstract: To identify correlates of Asian American professional help-seeking, we tested a mediation model describing Asian American help-seeking (Asian value of emotional self-control → help-seeking attitudes → willingness to see a counselor; Hypothesis 1) in a sample of Asian American college students from the Pacific Northwest region of the United States (N = 232). We also examined biological and spiritual etiology beliefs as moderators of the mediation model (Hypotheses 2a and 2b). Our findings indicated that help-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 57 publications
5
37
0
Order By: Relevance
“…A sample item is “I would want to get psychological help if I were worried or upset for a long period of time.” Fischer and Farina () reported that ATSPPH‐SF scores highly correlated with the full‐scale scores from the original measure, produced a good internal consistency coefficient (α = .84), and predicted past help seeking. The ATSPPH‐SF has demonstrated good internal consistency coefficients in samples of racially/ethnically diverse community adults (Gloria, Castellanos, Segura‐Herrera, & Mayorga, ) and college students (P. Y. Kim & Kendall, ). In the present study, we averaged item responses to generate a scale score and obtained an adequate internal consistency coefficient (α = .83).…”
Section: Methodsmentioning
confidence: 99%
“…A sample item is “I would want to get psychological help if I were worried or upset for a long period of time.” Fischer and Farina () reported that ATSPPH‐SF scores highly correlated with the full‐scale scores from the original measure, produced a good internal consistency coefficient (α = .84), and predicted past help seeking. The ATSPPH‐SF has demonstrated good internal consistency coefficients in samples of racially/ethnically diverse community adults (Gloria, Castellanos, Segura‐Herrera, & Mayorga, ) and college students (P. Y. Kim & Kendall, ). In the present study, we averaged item responses to generate a scale score and obtained an adequate internal consistency coefficient (α = .83).…”
Section: Methodsmentioning
confidence: 99%
“…Previous counseling experience was included as a covariate based on empirical findings in the literature (e.g., P. Y. Kim & Kendall, 2015). Results based on 5,000 bootstrapped resamples revealed a statistically significant indirect effect of -.04, because its bias corrected 95% CI [-.06, -.03] did not contain 0.…”
Section: Hypothesis 1: Test Of Mediationmentioning
confidence: 99%
“…These studies both viewed Asian Values as a single variable, but operationalized this variable as Emotional Self-Control. Kim and Kendall (2015) found that help-seeking attitudes mediated the relation between Emotional Self-Control and willingness to see a counselor.…”
Section: Chapter 4 Discussionmentioning
confidence: 93%
“…Currently, only two investigations (Kim & Kendall, 2015;Kim, Kendall, & Chang 2016) have focused exclusively on Emotional Self-Control when exploring the relationship between help-seeking attitudes and Asian American values. These studies both viewed Asian Values as a single variable, but operationalized this variable as Emotional Self-Control.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation